1998
DOI: 10.1063/1.120761
|View full text |Cite
|
Sign up to set email alerts
|

Uniform multiatomic step arrays formed by atomic hydrogen assisted molecular beam epitaxy on GaAs (331) substrates

Abstract: Growth kinetics and modeling of selective molecular beam epitaxial growth of GaAs ridge quantum wires on prepatterned nonplanar substrates Focused ion beam patterned Hall bars and Ohmic columns embedded in molecular-beam-epitaxial-grown GaAs/AlGaAs Molecular beam epitaxial growth of InAs/AlGaAsSb deep quantum well structures on GaAs substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…The surface morphology of the a-plane GaN film is quite rough with stripe feature along the [0 0 0 1] direction. It was reported that stripes were naturally formed during molecular beam epitaxy (MBE) of GaAs layers on GaAs (3 3 1) substrates and this feature was successfully used for fabricating quantum wires [10]. Though the stripe feature shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The surface morphology of the a-plane GaN film is quite rough with stripe feature along the [0 0 0 1] direction. It was reported that stripes were naturally formed during molecular beam epitaxy (MBE) of GaAs layers on GaAs (3 3 1) substrates and this feature was successfully used for fabricating quantum wires [10]. Though the stripe feature shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Though the stripe feature shown in Fig. 1(a) cannot be used for fabricating quantum wires because the lateral periodicity is too large, this feature is a potential method for fabricating quantum wires by adjusting the growth conditions as growth of GaAs layers on GaAs (3 3 1) substrates [10].…”
Section: Resultsmentioning
confidence: 99%
“…First, we can rule out the possibility that the surface undulation comes from the atomic steps of annealed rplane sapphire formed during annealing as the same surface features were obtained on unannealed sapphire substrates, which does not have those atomic steps on its surface. One possible explanation is that the surface undulation may be caused by the disparity of migration lengths of adatoms along the two perpendicular directions, c-and m-directions, during growth, as shown in the case of high-index GaAs surfaces such as GaAs (3 3 1) [10]. This disparity of migration length could be enhanced with increasing temperature, therefore resulting in more significant surface undulation for a-plane GaN films at elevated growth temperature.…”
Section: Article In Pressmentioning
confidence: 95%
“…22 The use of AH during GaAs ͑331͒ growth by MBE increases adatom mobility. 23 Further, the observation of improved LEED patterns that we report above may also be explained by enhanced adatom diffusion.…”
Section: Discussionmentioning
confidence: 78%